(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
Some of the rights enshrined in the ECHR are absolute (the prohibition of torture (Article 3), the prohibition of slavery and forced labor (Article 4)). It means that they can under no circumstances be restricted or reduced. All other rights may be partially restricted under the terms of Art. 15 of the ECHR, in cases of social urgency – martial / emergency within the limits necessary to prevent the threat to the life of the nation. Some ECHR articles explicitly state the conditions for restrictions on human rights and freedoms. So, the right to privacy (Art. 8), freedom of thought, conscience and religion (Art. 9), freedom of expression (Art. 10) and freedom of assembly (Art. 11) may be restricted, if required by the law and is necessary in a democratic society. Thus, conventional rights may also have inherent limitations. In particular, in some cases, the rights guaranteed by the various articles of the ECHR collide. Therefore, the main objective of this paper is to research the essence and core elements of the principle of proportionality in the jurisprudence of the ECtHR. To evaluate the proportionality of an interference with a right or freedom, it is necessary to determine its impact on the law, the causes of the interference, its results, the importance of local circumstances, and the complexity of objective evaluation of relevant rights and interests. It is the states that must justify such intervention. Herewith, the reasons should be ‘substantial and sufficient’, the need for the restriction ‘established by the law’, the exceptions ‘clearly stated’, and the interference must comply with ‘urgent social need’. According to the principle of proportionality, all legal actions and state decisions must be established by the law, necessary, relevant (suitable) and least restricts the right of the individual. In addition, the proportionality test must ensure that a person’s loss from the restriction of the right is commensurate with the benefit from the aim pursued. The balance is fair, if the restriction does not encroach on the very essence of the right and does not cause its real content to be lost. In assessing the proportionality of a state’s interference, the ECtHR applies the doctrine of the margin of appreciation, which can be broad or narrow. Thus, the principle of proportionality, which is closely linked to the principle of effective protection, significantly influences the case law of the ECtHR. Most of the disputes over proportionality arise in the context of human rights restrictions guaranteed by Articles 8 (2) – 11 (2) of the ECHR. Therefore, the principle of proportionality requires national public authorities to strike a fair balance between competing public and private interests at stake. The ECtHR assesses such factors, as the importance of competing interests, objectivity (adequacy, reasonableness) of the restriction, the existence of consensus among Council of Europe member States on the issue under consideration.